The Influence of Emotion on Cognitive Control: Relevance for Development and Adolescent Psychopathology - Mueller, Sven (Frontiers in Psychology, 2011)
The last decade has witnessed an explosion of research into the neural mechanisms underlying emotion processing on the one hand, and cognitive control and executive function on the other hand. More recently, studies have begun to directly examine how concurrent emotion processing influences cognitive control performance but many questions remain currently unresolved. Interestingly, parallel to investigations in healthy adults, research in developmental cognitive neuroscience and developmental affective disorders has provided some intriguing findings that complement the adult literature. This review provides an overview of current research on cognitive control and emotion interactions. It integrates parallel lines of research in adulthood and development and will draw on several lines of evidence ranging from behavioral, neurophysiological, and neuroimaging work in healthy adults and extend these to work in pediatric development and patients with affective disorders. Particular emphasis is given to studies that provide information on the neurobiological underpinnings of emotional and cognitive control processes using functional magnetic resonance imaging. The findings are then summarized and discussed in relation to neurochemical processes and the dopamine hypothesis of prefrontal cortical function. Finally, open areas of research for future study are identified and discussed within the context of cognitive control emotion interactions.